Review to Understand the Crosstalk between Immunotherapy and Tumor Metabolism - Pratibha Pandey; Fahad Khan; Tarun Kumar Upadhyay; Ramish Maqsood (Molecules, 2023)
Immune checkpoint inhibitors have ushered in a new era of cancer treatment by increasing the likelihood of long-term survival for patients with metastatic disease and by introducing fresh therapeutic indications in cases where the disease is still in its early stages. Immune checkpoint inhibitors that target the proteins cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) or programmed death-1/programmed death ligand-1 have significantly improved overall survival in patients with certain cancers and are expected to help patients achieve complete long-lasting remissions and cures. Some patients who receive immune checkpoint inhibitors, however, either experience therapeutic failure or eventually develop immunotherapy resistance. Such individuals are common, which necessitates a deeper understanding of how cancer progresses, particularly with regard to nutritional regulation in the tumor microenvironment (TME), which comprises metabolic cross-talk between metabolites and tumor cells as well as intracellular metabolism in immune and cancer cells. Combination of immunotherapy with targeted metabolic regulation might be a focus of future cancer research despite a lack of existing clinical evidence. Here, we reviewed the significance of the tumor microenvironment and discussed the most significant immunological checkpoints that have recently been identified. In addition, metabolic regulation of tumor immunity and immunological checkpoints in the TME, including glycolysis, amino acid metabolism, lipid metabolism, and other metabolic pathways were also incorporated to discuss the possible metabolism-based treatment methods being researched in preclinical and clinical settings. This review will contribute to the identification of a relationship or crosstalk between tumor metabolism and immunotherapy, which will shed significant light on cancer treatment and cancer research.